Design study and analysis of a conventional radial-field flux-switching permanent magnet machine for a medium-speed wind turbine - Pretorius, Dewald (Department of Electrical Engineering, 2021)
A conventional radial-field FSPM machine was designed and studied. The research focussed on the effectiveness of using a parametric study to obtain an optimized solution compared to using a computerized optimizer; as well as an in-depth core loss analysis. The designing process started with an analytical design that was used for initial design purposes, and this was followed by numerical simulations to get an optimized solution. Within the numerical simulations, the parametric analysis and optimization were performed. The final optimized design was designed to be manufactured and compared to both the analytical and numerical results for validation. The analytical and numerical results were obtained using MathWorks MATLAB 2019a and Ansys Maxwell 19.1 respectively. The results show that an optimizer is more effective in finding an optimized solution in the design space, however, the parametric analyses are still useful in order to determine the design regions for the optimizer and how sensitive certain parameters are towards the FSPM machine's performance. In the end, these analyses are used to speed up the design process by minimizing computational time, and also provides an understanding to the designer of parameter changes on the FSPM machine's performance.